MATHEMATICAL MODELING OF UNSTEADY FILTRATION OF ELASTIC LIQUID IN AN INHOMOGENEOUS RESERVOIR - A. G. Balamirzoev; A. M. Zerbaliev; V. V. Ivanov (Вестник Дагестанского государственного технического университета: Технические науки)
The article considers the possibility of numerical solution of two-dimensional problem of unsteady filtration in an inhomogeneous elastic liquid reservoir. The problem of finding the distribution of the pressure p(x,y,t) in the process of exploitation of deposits is reduced to the solution of a differential equation of parabolic type with variable coefficients. The problem is solved approximately by using the method of finite differences.